Rekonstruksi Hukum Perlindungan Lingkungan dan HAM dalam Konteks Climate Resilience - Rufinus Hotmaulana Hutauruk; Emiliya Febriyani; Nurlaily Nurlaily; N.A.D. Pramesti Anwar; Winda Fitri (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
The increasing frequency and intensity of climate change impacts, coupled with alarming risks of natural disasters, have spurred a global urgency to strengthen climate resilience. This research critically examines the readiness of Indonesia's legal landscape to support initiatives for enhancing climate resilience and the protection of human rights (HAM) in the context of environmental issues, considering Indonesia's vulnerable geographical position. Employing normative legal research methods, this study reveals that the regulatory framework for environmental management and protection in Indonesia has not fully provided the necessary legal certainty for climate change adaptation and mitigation efforts, nor has it optimally integrated human rights principles in addressing climate threats. As a solution, this research proposes a legal reconstruction model aimed at overcoming these shortcomings by establishing more robust legal certainty for enhancing climate resilience, while simultaneously placing human rights protection as a fundamental pillar in all related policies and actions. The implementation of this legal model necessitates public policy updates through the revision or enactment of more comprehensive and human rights-oriented legislation.